PENINGKATAN KEMAMPUAN SISWA KELAS VII SMP PERTIWI 1 PADANG DALAM MENENTUKAN GAGASAN UTAMA PARAGRAF DENGAN MENGGUNAKAN METODE JIGSAW - Dainur Putri (AT-TA'LIM, 2012)
Mixed method (quantitative and qualitative methods) was used to answer the research question that is there any significant improvement on students’ ability in determining main idea of a paragraph by using Jigsaw techniques?. The finding showed that there is significant effect on students’ ability in determining main ide of a paragraph by using Jigsaw technique. This finding was proved by the significant differences on students’ achievement between first cycle that is 78 and second cycle that is 84 (it implies that 97% of passing grade can be achieved). It can be concluded that this technique can be implemented by the Indonesian language teachers to improve students’ ability in determining main idea of the paragraphs.